LA RELACIÓN ENTRE DIVERSIDAD, GÉNERO Y CONTABILIDAD: THE RELATIONSHIP BETWEEN DIVERSITY, GENDER AND ACCOUNTING - Naranjo, David; Álvarez-Dardet Espejo, Concepción; Carrasco Gallego, Amalia (Revista de Contabilidad - Spanish Accounting Review, 2010)
Extensive studies in management literature may be found on the effects of diversity in organizations in general, and in work teams and boards in particular (Milliken and Martins, 1996; Jackson et al, 2003; see Carpenter, Geletkanycz and Sanders, 2004). Among these effects, we may highlight the positive influence of diversity on organizational management and performance, since diversity provides managers with a broader view of problems and a rich portfolio of responses to market demands, which facilitates swift recognition of strategic opportunities (Pitcher and Smith, 2001; Carpenter et al., 2004). Research on the distinction between heterogeneous vs. homogeneous boards has focused on analyzing how organizations face changes; arguing that homogenous boards facilitate rapid decision-making and reduce the risk of conflicts within a team. Furthermore heterogeneous boards also stimulate the search of new alternatives and courses of action that enable organizations to improve corporate performance (Finkelstein and Hambrick, 1996).